Dažas problēmas latviešu literārās valodas izveides procesā - Rozenbergs, Jānis (Baltistica, 1998)
SOME PROBLEMS OF THE FORMATION PROCESS OF THE LATVIAN LITERARY LANGUAGE0. Literary language is the most complete variety of language, manifesting its functions in the best way possible and unifying the nation, as well as representing national mentality among other nations and their languages.0.1. When speaking about the Latvian literary language and its formation, it seems useful to acknowledge that the literary language is (1) the language of the entire nation, (2) is being consciously cultivated and (3) has written form.0.2. When dealing with the Latvian literary language formation processes, one should take into consideration (a) the specific external (sociopolitical) conditions, (b) the sources of the literary language, (c) aspects of language development and its research.1. Development of the Latvian language has been affected by external sociopolitical factors and factors of migration of representatives of various cultural layers; these factors have both stimulated and hampered the overall formation of the language both in space and time.2. Research of the Latvian literary language is complicated, because the most reliable proofs of this process are written texts, which in Latvian appeared only in the 16th century. Therefore both folk-lore and the spoken language can be used as sources.2.1. From the 16th to the 19th century written texts were mainly produced by German clergymen who in the beginning (in the 16th century) had a poor knowledge of Latvian. Therefore these texts must be properly handled by differentiating the sociopolitical and philological activities of the Germans. Beginning with the 17th century a normative approach has been consciously applied to the language and thus a common variety of the language is being created by maximally keeping aloof of various patois forms.2.2. The source of analysis of the literary language and the process of its formation is the abundant Latvian folk-lore and especially the folk-songs (dainas), but the folk-lore language changes gradually from generation to generation.2.3. In studying the formation of the literary language, the spoken language found in written monuments and recorded in special questionnaires can be used.3. In inquiring about the Latvian literary language and its formation, definite layers of cognition can be traced: 1) statement and description of phonetic, lexical and grammatical phenomena found in the Latvian language and in the Latvian texts written by the German clergymen, 2) historical survey of language phenomena and their comparison with related languages, 3) analysis of the old-Latvian (and later also new-Latvian) written language, 4) analysis of colloquial Latvian and folk-lore, 5) fundamental synchronic and diachronic research in phonetics, word stock and grammar within the framework of the language norm, style and language culture aspects.3.1. None of these layers give an all-embracing picture of the stages of the development of the Latvian literary language, because in those days no such task was formulated.3.2. In Latvian linguistics the Latvian literary language formation problem became topical in the 50ies of the 20th century with the emergence of historical research of literary Latvian as an independent branch of linguistics.
Keywords: latvių kalba; bendrinė kalba